Urbanization favors the proliferation of Aedes aegypti and Culex quinquefasciatus in urban areas of Miami-Dade County, Florida - André B. B. Wilke (Nature Portfolio, 2021)
Abstract Urbanization processes are increasing globally. Anthropogenic alterations in the environment have profound effects on biodiversity. Decreased biodiversity due to biotic homogenization processes as a consequence of urbanization often result in increased levels of mosquito vector species and vector-borne pathogen transmission. Understanding how anthropogenic alterations in the environment will affect the abundance, richness, and composition of vector mosquito species is crucial for the implementation of effective and targeted mosquito control strategies. We hypothesized that anthropogenic alterations in the environment are responsible for increasing the abundance of mosquito species that are adapted to urban environments such as Aedes aegypti and Culex quinquefasciatus. Therefore, our objective was to survey mosquito relative abundance, richness, and community composition in Miami-Dade County, Florida, in areas with different levels of urbanization. We selected 24 areas, 16 remote areas comprised of natural and rural areas, and 8 urban areas comprised of residential and touristic areas in Miami-Dade County, Florida. Mosquitoes were collected weekly in each area for 24 h for 5 consecutive weeks from August to October 2020 using BG-Sentinel traps baited with dry ice. A total of 36,645 mosquitoes were collected, from which 34,048 were collected in the remote areas and 2,597 in the urban areas. Our results show a clear and well-defined pattern of abundance, richness, and community composition according to anthropogenic modifications in land use and land cover. The more urbanized a given area the fewer species were found and those were primary vectors of arboviruses, Ae. aegypti and Cx. quinquefasciatus.